Rituximab Use in the Management of Childhood Nephrotic Syndrome - Kallash, Mahmoud; Smoyer, William E.; Mahan, John D. (Frontiers in Pediatrics, 2019)
Pediatric nephrotic syndrome is a challenging and often persistent renal disorder and its incidence varies between different ethnicities and regions. Corticosteroids have been the main treatment for decades and are effective in most children with INS, although 10-15% of these children become steroid resistant. Furthermore, some initially steroid sensitive patients follow a steroid dependent or frequently relapsing course and are therefore at increased risk for developing steroid toxicity and disease progression. In such children, other immunosuppressive medications are used to achieve and/or maintain remission of NS. Rituximab, a monoclonal antibody directed against the B lymphocyte CD20 marker induces depletion of B cells, and has shown promising results in the management of NS in children. In this review, we summarize recent studies on the efficacy and safety of rituximab in the different types of pediatric NS, the known and potential mechanisms of action of rituximab, and the available and potential future biomarkers of rituximab activity.